Metal forming 2014 selected, peer reviewed papers from the 15th International Conference on Metal Forming 2014, September 21-24, 2014, Palermo, Italy - Fratini, Livan; Micari, Fabrizio (Key engineering materials ;, 2014)
Collection of selected, peer reviewed papers from the15th International Conference on Metal Forming 2014, September 21-24, 2014, Palermo, Italy . The 159 papers are grouped as follows: 1. COATINGS AND SURFACES, 2. EXTRUSION AND DRAWING, 3. FORGING, 4. FORMABILITY, 5. INCREMENTAL FORMING, 6. JOINING AND BONDING, 7. MAGNESIUM FORMING, 8. NUMERICAL MODELLING, 9. TUBE AND HYDRO FORMING, 10. OPTIMISATION, 11. OTHER PROCESSES, 12. POWDER AND ADVANCED MATERIALS, 13. ROLLING, 14. SHEARING, 15. SHEET METAL FORMING, 16. TITANIUM FORMING About 160 papers from more than 20 countries describe the state of metalforming around the world. The keynote addresses cover advanced in-process control systems for sheet stamping and tube hydroforming processes, andbeta-forging titanium Ti6Al4V alloy powders: phase evolution modeling and strain-rate relation. The other areas discussed are coatings and surfaces,extrusion and drawing, forging, formability, incremental forming, joining and bonding, magnesium forming, numerical modeling, tube and hydro forming,optimization, other processes, powder and advanced materials, rolling, shearing, sheet metal forming, and titanium forming. -- Engineering-- Materials science-- Metals.